The effect of racial prejudice on perceptions of Black slurs used by Black individuals toward White individuals - O'Dea, Conor James (Kansas State University, 2017)
The current research examined whether participants’ levels of racial prejudice impact their perceptions of a Black racial slur (“nigga”) used by a Black individual toward a White individual. The “racism justification hypothesis” predicts racial prejudice will be negatively related to perceptions of offensiveness due to motivations to trivialize racial slurs which allows for increased use of the slur by individuals higher in prejudice. The “hierarchy defense hypothesis” predicts racial prejudice will be positively related to more negative perceptions of the slur due to White individuals seeking to resist affiliation with Black individuals and perceiving affiliative attempts as threatening. Consistent with the hierarchy defense hypothesis, the results showed racial prejudice predicted greater offensive and negatively expressive perceptions, and lower positively expressive perceptions following “nigga” being used by a Black individual toward a White individual (Study 1). In Study 2, the current research examined whether motivations to trivialize racial slurs (i.e., racism justification) versus participants’ experiences of threat (i.e., hierarchy defense) mediated the relationships between racial prejudice and perceptions of “nigga” used by a Black individual toward a White individual. Consistent with the hierarchy defense hypothesis, racial prejudice, through status hierarchy threat, predicted greater offensive and negatively expressive perceptions, and lower positively expressive perceptions. The racism justification hypothesis was also supported. Participants’ levels of racial prejudice, through racism trivialization, were generally related to lower perceptions of the slur as offensive and greater perceptions of the slur as positively expressive. The current research then examined participants’ perceptions of “nigga” reciprocated by the White individual toward the Black individual. Interestingly, racial prejudice, through status hierarchy threat, predicted greater offensive and negatively expressive perceptions and lower positively expressive perceptions. Racial prejudice, through racism trivialization, predicted generally lower offensive perceptions and greater positively expressive perceptions. Thus, participants may have used their experiences of threat as justification for explicit prejudice toward the Black individual (i.e., perceiving the slur as more offensive and negative), while individuals who experienced trivialization motivations attempted to decrease their experiences of suppression factors by perceiving the slur as less offensive, allowing for increased use of the slur. Implications for these findings are discussed.
Keywords: Racial slurs; Slur reappropriation; Prejudice; Derogation; Affiliation; Intergroup processes